The "killer cell story" in recurrent miscarriage: Association between activated peripheral lymphocytes and uterine natural killer cells. (February 2017) - Kuon, R.J.; Vomstein, K.; Weber, M.; Müller, F.; Seitz, C.; Wallwiener, S.; Strowitzki, T.; Schleussner, E.; Markert, U.R.; Daniel, V.; Toth, B.
Highlights: Peripheral NK cells (NK) are elevated in patients with primary recurrent miscarriage. Patients with idiopathic recurrent miscarriage present elevated uterine NK (uNK). High DR+ peripheral lymphocytes are associated with high uNK. Activated NK, B and T cells might provide cytokines for the differentiation of uNK. Abstract: Peripheral and uterine NK cells (pNK, uNK) can be distinguished according to their receptor expression. Recent studies indicate an association of elevated pNK and uNK with recurrent miscarriage (RM). This study aimed to analyze pNK and uNK in patients with RM and healthy controls. Out of n = 590 RM patients screened according to a standard diagnostic protocol, n = 268 couples with ≥3 consecutive RM were identified. Subgroups consisted of n = 151 primary RM (pRM), n = 85 secondary RM (sRM), n = 32 tertiary RM (tRM) and n = 42 healthy controls. Finally, n = 147 idiopathic RM (iRM) and n = 121 non-iRM patients were identified. Peripheral blood levels of CD45 + CD3-CD56 + CD16+ NK cells were determined in non-pregnant patients and controls in the mid-luteal phase by FACS. In n = 129 RM patients a uterine biopsy was taken to evaluate CD56+ NK cells by immunohistochemistry. PRM showed higher absolute pNK than sRM (median/μl (Q1;Q3): 234 (147;306) vs 176 (128;245), p = 0.02). Further a trend towards higher pNK percentages in pRM was detected. UNK numbers did not differ between RM subgroups and did not correlate with pNK. However, the rate of highly elevated uNK was increased in iRM compared to non-iRM patients (p = 0.04). Further, higher numbers of CD45 + CD3-DR+ (p < 0.01) and CD45 + CD3 + CD8 + DR+ (p = 0.04) peripheral lymphocytes were associated with higher uNK numbers. In conclusion, elevated pNK were present in pRM patients. Although pNK and uNK numbers did not correlate, the association between high CD45 + CD3-DR+ and CD45 + CD3 + CD8 + DR+ peripheral lymphocytes and uNK might indicate that activated NK, B and T cells provide cytokines for the differentiation of uNK.